Sustainable livelihoods in protected areas: The case of Allspice (Pimenta Dioica) in the Maya Biosphere Reserve - Charry, Andres; Claros Trujillo, Luisa María; Wiegel, Jenny (2023)
The Maya Biosphere Reserve (MBR) In Peten, Guatemala comprises part of the 5 great forests of Mesoamerica, and has been a model for community-managed forests in the region since 1990. Thousands of families rely on timber and non-timber products from the MBR for their livelihoods. Local communities, public, private and cooperation actors have been developing sustainable forest value chains to improve local livelihoods as means to ensure its conservation, as cattle production, wildfires and agricultural expansion increase the pressure on the reserve. Allspice (Pimenta dioica) has been gaining traction due to its increasing demand and prices. Nevertheless, key information for improving the value chain is scarce and disperse.